2020
DOI: 10.3390/molecules25194579
|View full text |Cite
|
Sign up to set email alerts
|

Verbascoside-Rich Abeliophyllum distichum Nakai Leaf Extracts Prevent LPS-Induced Preterm Birth Through Inhibiting the Expression of Proinflammatory Cytokines from Macrophages and the Cell Death of Trophoblasts Induced by TNF-α

Abstract: Background: Preterm birth is a known leading cause of neonatal mortality and morbidity. The underlying causes of pregnancy-associated complications are numerous, but infection and inflammation are the essential high-risk factors. However, there are no safe and effective preventive drugs that can be applied to pregnant women. Objective: The objectives of the study were to investigate a natural product, Abeliophyllum distichum leaf (ADL) extract, to examine the possibility of preventing preterm birth caused by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Human villous trophoblast HTR‐8/SVneo was purchased from Procell (China) and cultured routinely in RPMI 1640 medium (Nacalai Tesque, Kyoto, Japan) containing 5% fetal bovine serum (FBS) (Sigma‐Aldrich) at 37˚C in an atmosphere consisting of 5% CO 2 and 95% air. To induce disorders and explore miRs responding to Pue treatment in dys‐functioned trophoblasts, the cells were firstly exposed to 1 μg/mL TNF‐α for 72 h 23 and then treated with 50 μg/mL Pue (purity > 98%, Sigma‐Aldrich, St. Louis, USA) for 24 h (concentration selected based on data in Figure S1). To determine miRs expression levels under Pue treatment, the cells after Pue treatment were collected, and total RNA in cells treated with TNF‐α alone or with Pue together was extracted using Trizol method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human villous trophoblast HTR‐8/SVneo was purchased from Procell (China) and cultured routinely in RPMI 1640 medium (Nacalai Tesque, Kyoto, Japan) containing 5% fetal bovine serum (FBS) (Sigma‐Aldrich) at 37˚C in an atmosphere consisting of 5% CO 2 and 95% air. To induce disorders and explore miRs responding to Pue treatment in dys‐functioned trophoblasts, the cells were firstly exposed to 1 μg/mL TNF‐α for 72 h 23 and then treated with 50 μg/mL Pue (purity > 98%, Sigma‐Aldrich, St. Louis, USA) for 24 h (concentration selected based on data in Figure S1). To determine miRs expression levels under Pue treatment, the cells after Pue treatment were collected, and total RNA in cells treated with TNF‐α alone or with Pue together was extracted using Trizol method.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of Pue on trophoblasts further confirmed its antagonizing function against PE development. Based on the study performed by Kim et al, the inflammatory responses associated with PE were the major factor impairing the mobility of trophoblasts 23.…”
mentioning
confidence: 99%
“…The PI3K/AKT pathway is expressed by growth factors that determine cell proliferation and apoptosis. In addition, the extract of A. distichum also suppresses overexpressed PI3K/AKT, thereby controlling cell death and cell proliferation [ 31 ]. BPH develops due to the indiscriminate proliferation of stromal cells and epithelial cells caused by AR signaling [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…'s study [ 25 ], the LD50 value was judged to be more than 2,000 mg/kg because A. distichum leaves did not show genotoxicity in mice. In a recently reported study, A. distichum has showed efficacy in anti-osteoporosis [ 27 ], anti-colorectal cancer [ 28 ], anti-melanoma [ 29 ], anti-DNA damage related oxidative stress [ 30 ], anti-inflammatory [ 31 ] and anti-obesity [ 32 ]. On the other hand, no research results have been reported on BPH using A. distichum .…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown of GPR91 had effect on the reduction of IL1b-mediated rather than TNF-mediated CCL2 mRNA expression and secretion, which might attribute to their recruitment of different messengers to regulate downstream genes (149). Other experiments focusing on the therapy of PTL mainly acted on different targets but ended up with NF-kB signal pathway to decrease the secretion of CCL2 (150)(151)(152). Therefore, CCL2 seems to make a difference in terminal inflammatory pathway and it is worth intensive studying how CCL2 exerts its function (153).…”
Section: Preterm Labormentioning
confidence: 99%